(untitled) (UNIZIK Journal of Marketing, 2024)
This study investigated the role of technology in enhancing ERP’s impact on organizational performance in Nigerian banks. The study utilized a cross-sectional survey research design and a regression analysis to examine how technology moderate the impact of ERP on the performance of Nigerian Banks. The technology acceptance model was used to underpin the study. The population of the study was the fourteen (14) quoted deposit money banks listed on the floor of the Nigerian stock exchange. The census study was adopted; hence the population was fully studied. However, five managers from marketing, operations, human resources, asset management and research/planning in each bank constituted the respondents of the study. Hence, seventy (70) managers were employed for the study. Data were collected through primary sources, seventy (70) copies of the questionnaire were distributed to the respondents after being pilot tested for validity and reliability. The research study made use of univariate and multivariate statistics for the analysis of data with the aid of the statistical package for social sciences (SPSS), version 25.0. The findings of the study revealed that technology positively and significantly moderates the influence of enterprise resource planning on organizational performance in the context of quoted deposit money banks in Nigeria. The study conclude that technology enhance resource planning and improves performance of quoted deposit money banks in Nigeria. We therefore recommend that management of the banks should make viable investments in technologies such as cloud-based ERP solutions and advanced analytics’ tools to enhance real-time decision making. This will significantly improve banks’ performance in the financial services market,